Business under adverse home country institutions: The case of international sanctions against Myanmar - Meyer, K.; Thein, Htwe Htwe (Vicky) (Pergamon, 2013)
We expand the institutional perspective of international business by exploring the range of institutions outside the host country that influence international business. We use a critical case, Myanmar, to explore the dynamics of institutional constraints and the reaction of business to such constraints. Our in-depth case analysis focuses on four industries for the period 1996–2011. On this basis, we develop the concept of ‘low profile strategy’ and propose a conceptual framework of home country pressures influencing multinational enterprises’ international operation, and the variation of their impact across industries and firms. This framework provides a foundation for future work on the extra-territorial effects of institutions in international business.